Kun-mkhyen Go-bo Rab-ʼbyams-pa Bsod-nams-seṅ-geʼi bkaʼ ʼbum - Go-rams-pa Bsod-nams-seṅge, 1429-1489 (Sakya College, 1979)
Collected works of a philosopher of the Sakyapa tradition of Tibetan Buddhism.